Corporate strategy implementation : how strategic plans become individual strategic actions across organizational levels of the MNC - Šilenskytė, Aušrinė (Vaasan yliopisto, 2020)
Managers often cite strategy implementation as the number one challenge in strategic management. Nevertheless, the topic has attracted relatively little attention, and particularly so from the perspective of how individual strategic behaviors emerge that result in successful implementation. Addressing the need to bring in the individual to improve our understanding of these processes, this dissertation aimed to examine how the corporate strategy of a loosely coupled MNC becomes (or otherwise) strategic behaviors of its managers and non-management employees across different levels of the organization. The dissertation investigated one Finnish MNC and the implementation of its corporate strategic goal “Working as ‘One Corporation’’’ within three of the MNC’s units: The headquarters in Finland, and two of its foreign subsidiaries in India and Russia. The embedded qualitative case study comprises 50 in-depth interviews with top and middle-level managers and non-management employees connected by one global project; and a large set of secondary data. Applying critical realism (CR), the findings illustrate how the interplay of the three realities (the Real, the Actual, and the Perceived) of the MNC served to create an environment in which individuals performed their (non-)strategic behaviors. The study reveals two theoretical mechanisms—commitment and reciprocity—through which strategic behaviors emerged, and also provides illustrations of how these mechanisms interacted with enabling or inhibiting entities. The dissertation contributes to the IB literature in several ways. It advances the Multilevel view of the MNC, which addresses theory development on the nested arrangements that exist within the MNC. It provides a systematic conceptualization of eclectic research on strategy implementation in MNCs, and sheds light empirically on the bottom-up processes that help to explain cross-level, cross-border interactions. In addition, the dissertation offers evidence of how the critical realism philosophy of science can be beneficial in studies on microfoundations, develops a method for CR application in fieldwork within the MNC, and illustrates its utility through this empirical study.

Johtajat mainitsevat usein strategian toteuttamisen strategisen johtamisen suurimpana haasteena. Aihe on kuitenkin siihen nähden herättänyt suhteellisen vähän huomiota, etenkin onnistuneen strategian toteuttamisen tuloksena ilmenevien yksilöllisten strategisten käytäntöjen suhteen. Väitöstutkimuksen tarkoituksena onkin selvittää, kuinka löyhän monikansallisen yrityksen yritysstrategia muovautuu (tai ei muovaudu) sen johdon ja työntekijöiden strategisiksi käytösmalleiksi. Väitöskirjassa tutkittiin suomalaista monikansallista yritystä ja sen yritysstrategian tavoitteen ”Working as 'One Corporation”' toteutumista sen kolmessa yksikössä: Suomen pääkonttorissa ja kahdessa tytäryhtiössä Intiassa ja Venäjällä. Väitöskirjan kvalitatiivinen tapaustutkimus käsittää 50 syvähaastattelua ylimmän ja keskitason johtajien sekä muiden työntekijöiden kanssa, joita kaikkia yhdistää sama kansainvälisen tason projekti, sekä suuren määrän toissijaista tietoa. Kriittistä realismia (CR, Critical Realism) soveltamalla havainnot kuvaavat, kuinka monikansallisen yrityksen kolmen todellisuuden (todellisen, aktuaalisen ja havaitun) vuorovaikutus luo ympäristön, jossa yksilöt suorittivat (ei-)strategisen käyttäytymisensä. Tutkimus paljastaa kaksi teoreettista mekanismia – sitoutumisen ja vastavuoroisuuden – joiden kautta strateginen käyttäytyminen syntyi, ja tarjoaa myös esimerkkejä näiden mekanismien vuorovaikutuksesta mahdollistavien tai estävien tekijöiden kanssa. Väitöskirja tuo osuuttaan IB-kirjallisuuteen monin tavoin. Se kehittää monikansallisten yritysten monitasoista näkymää, joka käsittelee yritysten sisäisten sisäkkäisten järjestelyjen teorian kehitystä. Se tarjoaa systemaattisen käsityksen eklektisestä tutkimuksesta strategian toteuttamiseksi monikansallisissa yrityksissä ja valaisee empiirisesti alhaalta ylöspäin suuntautuvia prosesseja, jotka auttavat selittämään rajat ylittävää vuorovaikutusta. Lisäksi väitöskirja tarjoaa todisteita siitä, miten tieteen kriittinen realismifilosofia voi olla hyödyllistä käyttäytymisen ja päätöksenteon mikroperustan tutkimuksissa, kehittää menetelmän kriittisen realismin soveltamiseksi monikansallisten yritysten kenttätyössä ja kuvaa sen hyödyllisyyttä tämän empiirisen tutkimuksen avulla.
Yrityksen strategian toteuttaminen : kuinka strategisista suunnitelmista tulee yksittäisiä strategisia toimia kautta monikansallisen yrityksen organisaatiotasojen
Keywords: strategy implementation; multinational; microfoundations; critical realism; case study; strategic behaviors; transnational MNC; global work; international corporations; enterprises; corporate strategies; leadership (activity); organisations (systems); strategic leadership; fi=Kansainvälinen liiketoiminta|en=International Business|